Percutaneous Transluminal Mitral Commissurotomy in Nepalese children with Rheumatic Mitral Stenosis - Shrestha, Manish; Adhikari, Chandra Mani; Shakya, Urmila; Khanal, Aayush; Shrestha, Shradha; Rajbhandari, Rajib (Nepalese Heart Journal, 2014)
Background: Rheumatic heart disease is one of the most common heart diseases in developing country; however rheumatic mitral stenosis in children is relatively rare. Percutaneous transluminal mitral commissurotomy is a well established therapeutic intervention for mitral stenosis in adults. The study is conducted to determine the efficacy and safety of PTMC in children with severe mitral stenosis. Methods: A single centre retrospective study is conducted over a 3 and half years period (from 16th November, 2009 to 15th May, 2013) in Shahid Gangalal National Heart Centre, Kathmandu, Nepal. All consecutive patients aged less than 15 years who underwent Percutaneous transluminal mitral commissurotomy for severe mitral stenosis were included. Mitral valve area, left atrial pressure and mitral regurgitation were compared pre and post procedure. Results: During the study period, 2237 patients underwent Percutaneous transluminal mitral commissurotomy. Among them 100 children less than 15 years of age were included. Successful results were obtained in 94 (94%) patients. Mitral valve area increased from 0.7±0.15 cm2 to 1.5±0.32 cm2 (p<0.001). A significant decrease in left atrial pressure was observed from 29±7.9 mmHg to 13.9±6.2 mmHg (p<0.001). There was no significant change in grade of post procedural mitral regurgitation. Conclusions: Percutaneous transluminal mitral commissurotomy in children with severe mitral `stenosis is safe, effective and should be considered as procedure of choice for childrens. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 23-26 DOI: http://dx.doi.org/10.3126/njh.v10i1.9743